Angiopoietin-2 is Vasoprotective in the Acute Phase of Cerebral Ischemia. Issue 3 (March 2013) - Marteau, Léna; Valable, Samuel; Divoux, Didier; Roussel, Simon A; Touzani, Omar; MacKenzie, Eric T; Bernaudin, Myriam; Petit, Edwige
Most forms of cerebral ischemia are characterized by damage to the entire neurovascular unit, which leads to an increase in the permeability of the blood–brain barrier (BBB). In response to permanent focal cerebral ischemia in mice, we detected an early concomitant increase in the expression of the vascular endothelial growth factor (VEGF), a key inducer of vascular leakage and pathological blood vessel growth, and of angiopoietin-2 (Ang2), which is closely associated with VEGF in vascular remodeling. Thus, the aim of this study was to evaluate the role of Ang2 alone, or in combination with VEGF, in the acute phase of cerebral ischemia. The effect of these angiogenic factors on the ischemic lesion volume was evaluated by magnetic resonance imaging. We observed that timely administration of VEGF exacerbates ischemic damage. In contrast, Ang2 decreases the ischemic volume and this beneficial effect is maintained in the presence of VEGF. This investigation reports, for the first time, a protective role of Ang2 following cerebral ischemia, an action associated with a reduced BBB permeability. We propose that Ang2 represents a pertinent molecular target for the treatment of cerebral ischemia since acute brain damage may be limited by a pharmacological protection of the vascular compartment.